1998
DOI: 10.7748/ns.12.16.43.s49
|View full text |Cite
|
Sign up to set email alerts
|

Using training needs analysis to implement change

Abstract: This article describes the application of a systematic approach to training needs analysis prior to a major change in practice. The authors suggest that such a systematic approach is a central component in the successful management of change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This point has been more broadly supported by other writers, who have suggested that the potential recipients of training are the most appropriate definers of the course provision (Burnes 1996, Gibson 1998). Therefore, full and systematic training needs analysis conducted with the population of potential course participants is a critical first step in planning and implementing educational change (Fyffe & Fleck 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This point has been more broadly supported by other writers, who have suggested that the potential recipients of training are the most appropriate definers of the course provision (Burnes 1996, Gibson 1998). Therefore, full and systematic training needs analysis conducted with the population of potential course participants is a critical first step in planning and implementing educational change (Fyffe & Fleck 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that a sound training needs assessment instrument is required, which can inform educational providers both about course content and level, as well as the most suitable participants (Atkin et al . 1994, Fyffe & Fleck 1998). Thus far, no such instrument exists, a fact due in no small way to the recency of these initiatives.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of strategies have evolved including scenario role playing, video information, outreach programs, and specially devised programs where patients have contact with health professionals over differing periods of time (22)(23)(24)(25)(26)(27). The focus of these strategies has been to encourage selfmanagement based on health behavior theories.…”
Section: Asthma Patient Education Self Management Research Issuesmentioning
confidence: 98%
“…Methods of data collection The method of data collection must be rigorous yet practical. TNA is conducted because of the need to tackle a genuine problem such as how to implement a new computer system for staff to use in the clinical areas Conducting training needs analysis january 28/vol18/no20/2004 nursing standard 35 art&scienceeducation and training (Fyffe and Fleck 1998) or how to ensure that a particular university course meets the needs of staff in delivering care for a specific client group (Smith and Topping 2001). A range of methods can be used, including: face-to-face interviews; telephone interviews; focus groups; documentary analysis; observation; and questionnaires.…”
Section: Online Archivementioning
confidence: 99%